On Educational Excellence - Terzi, Lorella (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2020)
In recent decades, the pursuit of excellence, broadly defined as high educational achievement, has shaped the education systems and the research agendas of many countries across the world. Schools have been encouraged to provide a world-class quality education, with an emphasis on outstanding performance for some students, alongside a general improvement of outcomes for all. Educational excellence is however a very debated ideal. Given the complexities of defining ‘excellence,’ questions arise about its precise meaning in relation to achievement but also, and importantly, about its significance for education. This paper examines excellence as an ideal for education policy and the reasons for pursuing it. It suggests that educational excellence ought to be conceived in ways that are conducive to a general aim of well-being for all, in various abilities that lead to valuable pursuits, with due consideration of the importance of high achievement in relation to individuals’ specific aptitudes.